2018
DOI: 10.4236/as.2018.91008
|View full text |Cite
|
Sign up to set email alerts
|

Planting Geometry Effects on the Growth and Yield of Dryland Cotton

Abstract: The declining Ogallala Aquifer beneath the Southern High Plains may necessitate dryland crop production and cotton (Gossypium hirsutum L.) is a well-adapted and potentially profitable alternative crop. The limited growing season duration of the Texas Panhandle and southwestern Kansas, however, imposes significant production risk due to incomplete boll maturation. Emphasizing earlier boll production that is usually confined to sites on lower fruiting branches may reduce risk, but offsetting high planting densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Concerning fiber fineness, sowing cotton plants in beds with wide distance between hills (D3 pattern) recorded the best fineness of cotton fiber followed by sowing cotton plants in beds with narrow distance between hills (D4 pattern) without significant between them in the second season. These results are in accordance with Baumhard et al (2018) who showed that sowing cotton plants in wide furrows gave the highest values of fiber length in comparison with narrow furrows. However, Deshish (2021) stated that uniformity index, micronaire reading and pressley index were not significantly affected by plant distribution patterns.…”
Section: -Technological Characters Of Fibersupporting
confidence: 92%
“…Concerning fiber fineness, sowing cotton plants in beds with wide distance between hills (D3 pattern) recorded the best fineness of cotton fiber followed by sowing cotton plants in beds with narrow distance between hills (D4 pattern) without significant between them in the second season. These results are in accordance with Baumhard et al (2018) who showed that sowing cotton plants in wide furrows gave the highest values of fiber length in comparison with narrow furrows. However, Deshish (2021) stated that uniformity index, micronaire reading and pressley index were not significantly affected by plant distribution patterns.…”
Section: -Technological Characters Of Fibersupporting
confidence: 92%
“…For GOSSYM, previous model validation by Staggenborg et al (1996) demonstrated that the calculated daily water use was within one standard deviation of measured values and seasonal totals differed by ~10% for irrigated cotton under semiarid southern High Plains conditions. Similarly, the observed and modeled dryland lint yields at Bushland, Texas, about 180 km north agreed well with observations, achieving an RMSE that was ~20% of the mean yield (Baumhardt, 2002;Baumhardt et al, 2018). For Kansas, GOSSYM-estimated yields are plotted in figure 3 across overall means of as many as 49 cultivars from ongoing variety trials conducted near Hugoton, Kansas, 228 km NNE of Bushland.…”
Section: Model Uncertaintysupporting
confidence: 63%
“…Despite the possible N deficit, GOSSYM-simulated lint yields averaged ~90% of the mean observed yields of multiple cultivars, suggesting robust model performance that, taken in aggregate, shows reliable calculated yields. Validation of GOSSYM using local soil parameters and weather has been consistently successful at sites spanning a ~400 km distance from Lubbock to Bushland (Staggenborg et al, 1996;Baumhardt et al, 2018) and on to Hugoton. This suggests that model application for an additional ~250 km distance north from Hugoton to Colby can provide reasonable management inferences despite no further validation in lieu of variety performance data.…”
Section: Model Uncertaintymentioning
confidence: 95%
See 2 more Smart Citations